Integration, labor market regulation, lobbying, and technological change - Tapio Palokangas (Institute for the Study of Labor (IZA), 2009)
This paper examines an economic union where oligopolistic firms produce by skilled and unskilled labor and do in-house R&D by skilled labor. The planner of the union accepts new members to the union, regulates the labor market through a minimum wage for unskilled labor and supports firms by taxation. Firms and workers lobby the planner for prospective policy. It is shown that in the political equilibrium small unions regulate the labor market but do not support firms, while large unions deregulate the labor market and support firms.
urn:nbn:de:101:1-2009040394
Keywords: F15; J50; O40; 330; Economic integration; minimum wage; market power; endogenous technological change; Wirtschaftsintegration; Mindestlohn; Marktmacht; Interessenpolitik; Endogener technischer Fortschritt; Theorie